Transient contribution of left posterior parietal cortex to cognitive restructuring - Sutoh, Chihiro; Matsuzawa, Daisuke; Hirano, Yoshiyuki; Yamada, Makiko; Nagaoka, Sawako; Chakraborty, Sudesna; Ishii, Daisuke; Matsuda, Shingo; Tomizawa, Haruna; Ito, Hiroshi; Tsuji, Hiroshi; Obata, Takayuki; et al. (Scientific reports, 2015)
Cognitive restructuring is a fundamental method within cognitive behavioural therapy of changing dysfunctional beliefs into flexible beliefs and learning to react appropriately to the reality of an anxiety-causing situation. To clarify the neural mechanisms of cognitive restructuring, we designed a unique task that replicated psychotherapy during a brain scan. The brain activities of healthy male participants were analysed using functional magnetic resonance imaging. During the brain scan, participants underwent Socratic questioning aimed at cognitive restructuring regarding the necessity of handwashing after using the restroom. The behavioural result indicated that the Socratic questioning effectively decreased the participants' degree of belief (DOB) that they must wash their hands. Alterations in the DOB showed a positive correlation with activity in the left posterior parietal cortex (PPC) while the subject thought about and rated own belief. The involvement of the left PPC not only in planning and decision-making but also in conceptualization may play a pivotal role in cognitive restructuring.